Effects of heat on seven endodontic sealers - Chavarría Bolaños, Daniel (2022)
Purpose: To examine the microscopic surface features, chemical composition, and thermodynamic profile of seven endodontic sealers (AH Plus, Adseal, MTA-Fillapex, RoekoSeal, GuttaFlow 2, GuttaFlow BioSeal, and EndoRez) exposed to high-temperature changes using an endodontic obturation device. Methods: The thermal properties were examined using scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Then, six disc-shaped specimens of each sealer were prepared and divided into two groups – a room temperature group and a heat exposure group – for analysis of surface and chemical changes using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Results: DSC analysis showed that AH Plus had the highest exothermal signal (122.9°C), while TGA analysis showed that MTA-Fillapex was most affected by increased temperature (32.4% mass loss at 230ºC). SEM analysis showed that while AH Plus and GuttaFlow BioSeal maintained their surface integrity after heat exposure, the EDS profiles demonstrated changes in the chemical composition of the sealers after heat exposure for 5 s. High-temperature exposure had a negative impact on the properties of five of the sealers (Adseal, MTA-Fillapex, RoekoSeal, GuttaFlow 2, and EndoRez). Conclusion: AH Plus and GuttaFlow BioSeal showed minimal changes upon high-temperature exposure, suggesting their suitability for thermal endodontic obturation techniques.